The synthesis of some new sulphur containing heterocycles - Lee, C (1983)
Earlier work on the synthesis of thiophenes and thiophenophanes is reviewed. The main objective of the research was to synthesize cyclic sulphonium salts, such as (1) or (1, but m=n=CH=CH), where aromaticity might be shown and the normal tetrahedral configuration of sulphur might be flattened. Attempts to prepare (1O) and (11), precursors for (1) and an analogue, by cyclization of 2-substituted 2, 5-diphenylthiophenes failed. The main synthetic objective was (1, but m=n=CH=CH) . The diyne (3) was prepared, but conversion to (5) by hydrogen sulphide was not achieved. The synthesis of (4) was accomplished by coupling (12) with ethynyltrimethylsilane under new conditions to (12, but X=C=CSiMe3, which with n-Bu3SnH/Pd(PPh3)4, gave (13), a new type of selective reduction. Desilylation and intramolecular coupling afford (4), which is the first example of a dibenzo-fused {l3} annulenone having partially saturated double bonds. Sodium sulphide treatment yielded (14), but prior reduction to (4, but Y=CHOH) then yielded (6), the first example of a dibenzo-fused thiophenophane. This scheme leading to (6) could have wide application. The iodo and triflate derivatives of (6) decomposed to (7) with no sign of (1, but m=n=(CH 2)2), while (6, but Y= C=O)p-tosylhydrazone on LDA treatment gave (7), (7, but Y=ZCH=CH) and (8). Attempted dehydrogenation of (6, but Y= C=O) by DDQ or chloranil eliminated hydrogen sulphide yielding (4), while other reagents did not react or caused polymerization. A general synthesis of the ethynylaldehyde (15) was discovered in the synthesis of (16), a possible precursor of (2). Attempts to prepare (1, but m=CH=CH) were unsuccessful because of difficulties in synthesizing 2,5-disubstituted thiophenes of type (9) . Some experiments towards the synthesis of (17) were made. Compound (18) was prepared by a 7-stage synthesis and demethylated to (19). Oxidative demethylation of (18) and oxidation of (19) using various reagents did not give (2O). The thesis concludes with an experimental section (90 pages) and a bibliography (226 references). [Numbers in brackets in abstract refer to chemical diagrams. See pdf. for full abstract including these illustrations]